Isolation and Characterization of Nitrogen-Fixing Bacteria from Pineapple Rhizosphere on the Slopes of Mount Kelud Kediri - Dewi, Putri Rosfiana; Trimulyono, Guntur (LenteraBio : Berkala Ilmiah Biologi, 2023)
Non-symbiotic nitrogen-fixing bacteria can be isolated from the rhizosphere of various plants to obtain various types of bacteria with different nitrogen-fixing abilities. The purpose of this study was to isolate and characterize the rhizosphere bacterial isolates of pineapple (Ananas comosus) from the slopes of Mount Kelud, Kediri, and to determine their ability to fix nitrogen. Characterization based on the characteristics of colony morphology, cell morphology, Gram properties, motility, and catalase. A qualitative test of nitrogen-fixing ability was carried out using Nitrogen Free Bromothymol Blue medium and a quantitative test using the Nessler method and spectrophotometry. The results of the study obtained 4 isolates of nitrogen-fixing bacteria (P33, B21, B22, and B23 isolates) from 19 isolated isolates. The morphological characteristics of the colonies found varied; morphological characteristics of coccus and bacilli-shaped cells with mono and strepto cell arrangements. Three isolates were Gram-positive bacteria and one was Gram-negative bacteria. All isolates were motile and capable of producing the catalase enzyme. Nitrogen-fixing bacteria isolates can produce ammonium with an average concentration of 0.586 ppm (isolate P33); 0.917 ppm (isolate B21); 0.682 ppm (isolate B22); and 0.577 ppm (isolate B23). It is hoped that the superior nitrogen-fixing bacteria isolates can be further studied so that they can be applied as bio-fertilizer inoculums to realize sustainable agriculture.